UPPER FRASNIAN (UPPER DEVONIAN) POLYGNATHUS AND ICRIODUS CONODONTS FROM THE BAHRAM FORMATION, HUR SECTION, KERMAN PROVINCE, SOUTHEASTERN IRAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
Conodont fauna from the Upper Devonian (Frasnian) Bahram Formation at the Hur section, north of Kerman, southeast Iran, is dominated by species of Icriodus and Polygnathus. This fauna allowed discrimination of two biointervals from the Lower rhenana Zone to an Upper rhenana-linguiformis interval. The age of the lower part of the studied section is tentatively considered to be older than the Lower rhenana Zone.
Keywords: Frasnian; Biostratigraphy; Conodonts; Bahram Fm.; Kerman Province; Iran